Caspase-9 Is a Positive Regulator of Osteoblastic Cell Migration Identified by diaPASEF Proteomics - Říhová, Kamila; Lapčík, Petr; Veselá, Barbora; Knopfová, Lucia; Potěšil, David; Pokludová, Jana; Šmarda, Jan; Matalová, Eva; Bouchal, Pavel; Beneš, Petr (Journal of proteome research, 2024)
Caspase-9 is traditionally considered the initiator caspase of the intrinsic apoptotic pathway. In the past decade, however, other functions beyond initiation/execution of cell death have been described including cell type-dependent regulation of proliferation, differentiation/maturation, mitochondrial, and endosomal/lysosomal homeostasis. As previous studies revealed nonapoptotic functions of caspases in osteogenesis and bone homeostasis, this study was performed to identify proteins and pathways deregulated by knockout of caspase-9 in mouse MC3T3-E1 osteoblasts. Data-independent acquisition-parallel accumulation serial fragmentation (diaPASEF) proteomics was used to compare protein profiles of control and caspase-9 knockout cells. A total of 7669 protein groups were quantified, and 283 upregulated/141 downregulated protein groups were associated with the caspase-9 knockout phenotype. The deregulated proteins were mainly enriched for those associated with cell migration and motility and DNA replication/repair. Altered migration was confirmed in MC3T3-E1 cells with the genetic and pharmacological inhibition of caspase-9. ABHD2, an established regulator of cell migration, was identified as a possible substrate of caspase-9. We conclude that caspase-9 acts as a modulator of osteoblastic MC3T3-E1 cell migration and, therefore, may be involved in bone remodeling and fracture repair.
Keywords: Caspase 9; buněčné linie; genový knockout; migration; Cell Line; Proteomics; myši; Mice; Cell Movement; proteomics; zvířata; osteoblasty; diaPASEF; pohyb buněk; Animals; Osteoblasts; Gene Knockout Techniques; ABHD2; osteoblasts; kaspasa 9; proteomika